PENGEMBANGAN KAPASITAS TIM PENGGERAK PKK DAN KADER POSYANDU DALAM PEMBERIAN BANTUAN PELAYANAN KESEHATAN DASAR BAGI LANJUT USIA DI KELURAHAN SUKALUYU KECAMATAN CIBEUNYING KALER KOTA BANDUNG - Huraerah, Abu; Nurwulan, Riany Laila; Wahyu, Musihan; Hakim, Fakhri Ihsan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
This activity aims to (1) increase insight and knowledge about health for the elderly, especially about diseases that are often suffered by the elderly, namely cholesterol, uric acid, and blood sugar; (2) conduct health checks for the elderly, namely cholesterol, uric acid, and blood sugar; and (3) increase the capacity of driving team of the Family Empowerment and Welfare (Pemberdayaan dan Kesejahteraan Keluarga/PKK) and cadres of Integrated Service Post () in providing basic health service assistance for the elderly, Pos Pelayanan Terpadu/Posyandu especially in the use of manual health check tools (cholesterol, uric acid, and blood sugar). The implementation methods include outreach, health education, training facilitation, health checks, and monitoring and evaluation. The activities implemented included health checks for the elderly, which included outreach, training, and health checks to foster understanding and awareness of the importance of health and a healthy lifestyle. This results of activity are increase in understanding and awareness among driving team of PKK and caders of Posyandu about the importance of health, especially for the elderly. However, regular and ongoing exercise activities for the elderly are still needed as an integrated part of elderly health care.